Syphilis in Pregnancy and Congenital Syphilis: Reality in a Portuguese Central University Hospital - Magda Magalhães; Lígia Basto; Ana Luísa Areia; Sofia Franco; Maria Eugénia Malheiro; Maria Eulália Afonso; Paulo Moura (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Purpose To evaluate maternal-fetal surveillance and follow-up of infants at risk for congenital syphilis (CS). Methods Retrospective cohort study in a Portuguese Tertiary Referral Hospital. The main inclusion criterion was a positive syphilis serology. The study included all pregnant women that delivered in our hospital between January 2004 and December 2013. The neonates were classified according to their probability of infection based on the Centers for Disease Control and Prevention guidelines. Results Among the 27 pregnancies at risk for CS, 48.2% (n = 13) of the women had a diagnosis during the 1st trimester, and the median gestational age at the end of the treatment was 28 weeks. Inadequate treatment was noted in 44.4% (n = 12) of the women. Adverse pregnancy outcomes were observed in 30.8% of the cases (n = 8), 5 of which had been adequately treated. We found 2 (7.7%) cases with "proven or highly probable CS," 10 (38.5%) with "possible CS," 12 (46.1%) with "less likely CS," and 2 (7.7%) with "unlikely CS."Among the infants, the treatment was successful, except for 1 neurosyphilis case. Conclusion This study highlights many of the difficulties/concerns encountered in the maternal-neonatal management of syphilis. We highlight the importance of assuring the early detection of the infection as a way of guaranteeing the timely treatment, as well as a good compliance to the treatment and follow-up through a more efficient pregnant women surveillance network.